Pengaruh Pengalaman Kerja, Safety Morning Talk, Penggunaan APD, Terhadap Kinerja Karyawan Yang Dimoderasi Kecelakaan Kerja - Dian Mulyaningtyas; Yora Shaki Anwar (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This research aims to determine the effect of work experience, safety morning talk, and PPE on employee performance moderated by work accidents at PT. McDermott Indonesia. The research method used is quantitative research. Variables are measured using a Likert scale. The number of respondents in this research was 152 employees of PT. McDermott Indonesia, who works in the manufacturing sector. Data collection techniques use questionnaires and literature study. The data analysis technique uses Partial Least Square (PLS). This research indicates that work experience (X1) influences employee performance. Safety Morning Talk (X2) influences employee performance (Y). Meanwhile, using PPE (X3) does not affect employee performance (Y). After moderation, work experience (X1) influences employee performance (Y), which is moderated by the work accident variable (Z). Safety Morning Talk (X2) does not affect employee performance (Y), moderated by work accidents. In contrast, the use of PPE (X3) does not affect employee performance (Y), which is moderated by work accidents (Z).